Explorations in neuroscience, psychology, and religion - Seybold, Kevin S. (Ashgate science and religion series, 2007)
Neuroscience -- Psychology -- Religion -- Philosophy of science -- Integration issues -- Brain and religion -- The self -- Evolutionary psychology -- Religion/spirituality and health -- The future?